"Triple Phase" Budesonide Capsules for the Treatment of Olmesartan-Induced Enteropathy. (September 2014) - Hartranft, Megan E.; Regal, Randolph E.
Objective: To describe the treatment of a case of olmesartan-induced enteropathy in a patient with inflammatory areas widely distributed along the gastrointestinal tract.Case Summary: A 75-year-old patient presented with a 5-month history of recurrent severe diarrhea, diagnosed as olmesartan-induced enteropathy. A modified regimen of oral enteric-coated budesonide (EC-BUD), in combination with other antidiarrheal and anti-inflammatory therapies, was prescribed. The patient experienced rapid improvement in symptoms and was able to titrate off all enteropathy medications, including budesonide within 4 months after hospital discharge.Discussion: Olmesartan-induced enteropathy is a recently identified adverse effect of this angiotensin II receptor blocker. Oral budesonide is indicated for use in Crohn's disease to provide topical anti-inflammatory therapy without significant systemic steroid absorption. Budesonide, as enteric-coated oral 3-mg capsules, was chosen as therapy in this patient because of its localized effect and proven efficacy in gastrointestinal inflammatory disorders. The administration technique was modified to target areas of inflammation throughout the gastrointestinal tract.Conclusions: We postulate that this modified administration of EC-BUD may be an effective therapeutic modality for olmesartan-induced enteropathy. It may likewise be an appropriate adjunct to other conditions involving widespread gastrointestinal inflammation, including eosinophilic gastroenteritis and gastrointestinal graft versus host disease.